2012
DOI: 10.1111/ajco.12038
|View full text |Cite
|
Sign up to set email alerts
|

Combined temozolomide and radiation as an initial treatment for anaplastic glioma

Abstract: No significant benefit of combined TMZ with RT compared to RT alone was observed as the initial treatment of anaplastic glioma. Prospective randomized trials are needed to evaluate the optimal treatment for this disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 21 publications
1
4
0
1
Order By: Relevance
“…These tumors used to be included in trials together with glioblastoma as high-grade gliomas, and there have been few studies focused only on grade 3 glioma. Postoperative radiotherapy in combination with chemotherapy has improved the prognosis of highgrade glioma, with the median OS reported as two years for AA and four years for AO [6], although the prognosis is highly variable depending on factors such as the extent of resection and molecular markers [7][8][9]. The prognosis in our study was comparable to that in previous studies.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…These tumors used to be included in trials together with glioblastoma as high-grade gliomas, and there have been few studies focused only on grade 3 glioma. Postoperative radiotherapy in combination with chemotherapy has improved the prognosis of highgrade glioma, with the median OS reported as two years for AA and four years for AO [6], although the prognosis is highly variable depending on factors such as the extent of resection and molecular markers [7][8][9]. The prognosis in our study was comparable to that in previous studies.…”
Section: Discussionsupporting
confidence: 78%
“…Postoperative radiotherapy is usually indicated for both grade 3 glioma and grade 4 glioblastoma. However, the treatment results and tumor features of grade 3 glioma clearly differ from those of glioblastoma, but there is scarce data on outcomes and tumor progression for grade 3 glioma [1][2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Stupp and colleagues have reported that survival of patients who received the combination therapy of TMZ and radiation exceeded that of radiation alone [ 32 ]. Unfortunately, there is no significant benefit of using similar approach in our patient cohort [ 33 ]. This may be due to the small number of patient cohort, or perhaps, the genetic aberrations of Asian glioma patients differ from those of Caucasian glioma patients.…”
Section: Discussionmentioning
confidence: 99%
“…Until now, there have been limited trials examining the efficacy and safety of temozolomide for patients with WHO grade III gliomas based on prospective molecular stratification. Furthermore, for patients with WHO grade III gliomas, the addition of temozolomide to radiotherapy, rather than PCV, is unusual [24]. Available data demonstrate with fair clarity that temozolomide is less toxic, easier to prescribe and less complicated for patients [25].…”
Section: Discussionmentioning
confidence: 99%